Aesthetics of the Dramatic Art Theoretical Dramaturgy - Zich, Otakar (Karolinum, 2024)
Otakar Zich's Aesthetics of the Dramatic Art. Theoretical Dramaturgy (1931) laid the foundation of systematic modern theatre theory and helped establish theatre studies as an academic discipline. With an introduction, a contextual afterword and a glossary, this volume is the first complete translation into any language. Alongside Theatre Theory Reader. Prague School Writings (2016), it provides a thorough insight into Czech theatre thinking and a theory of theatre as a time-based art, perceived in the moment by an audience. Covering spoken drama and opera, Zich uniquely analyses the individual creative works that participate in making theatre.
Keywords: Ostatní